2007
DOI: 10.1111/j.1460-9568.2007.05949.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine and cognitive control: the prospect of monetary gains influences the balance between flexibility and stability in a set‐shifting paradigm

Abstract: Positive affect and the activity of the neurotransmitter dopamine seem to shift the balance between cognitive flexibility vs stability towards increased flexibility. Here we examined the impact of prospective monetary gains on this balance. Seventy healthy volunteers performed a set-shifting task comprising a condition in which a bias towards new stimuli helped to overcome perseveration and increased flexibility, and a second condition in which directing attention towards new stimuli increased distractibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 28 publications
6
81
0
Order By: Relevance
“…Instead, we believe that people's fastest task performance (as measured by RTs) and highest flexibility (as measured by switch costs) did not coexist in the same condition because flexibility trades off with stability-our tendency to stay on task (see Leber et al, 2008;Müller et al, 2007). The aforementioned researchers have suggested that when we are at our most flexible, we are actually not as prepared to perform a practiced task or primed response, which may help explain some cases of choking under pressure (e.g., Baumeister, 1984;Beilock & DeCaro, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we believe that people's fastest task performance (as measured by RTs) and highest flexibility (as measured by switch costs) did not coexist in the same condition because flexibility trades off with stability-our tendency to stay on task (see Leber et al, 2008;Müller et al, 2007). The aforementioned researchers have suggested that when we are at our most flexible, we are actually not as prepared to perform a practiced task or primed response, which may help explain some cases of choking under pressure (e.g., Baumeister, 1984;Beilock & DeCaro, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Switch costs can apparently diminish with monetary performance incentives, although those reported decreases were measured across two different experiments, conducted with different participants several years apart (Nieuwenhuis & Monsell, 2002). Other studies in which new stimuli have been introduced at the time of switching have suggested, instead, that monetary incentives encourage more stable, rather than flexible, behavior (Müller et al, 2007), although the researchers also reported that people who approached the task with relaxed and positive attitudes showed increased flexibility (see also Dreisbach & Goschke, 2004). Even though the field has recognized the relevance and usefulness of lowering switch costs in our increasingly complex lives (e.g., Leber et al, 2008;Logan, 2004;Wager et al, 2004), we are still lacking reliable and reasonably quick means for decreasing or at least modulating these costs.…”
Section: Experiments 1: Flexibility In Task Switchingmentioning
confidence: 99%
“…Persistence and flexibility have been considered two antagonistic metacontrol strategies (i.e., strategies that control cognitive control; Goschke, 2003;Cools & d'Esposito, 2011) that can be considered as the extreme poles of a common metacontrol dimension (Hommel, 2015). Changing tasks and environmental conditions require continuous readjustments of the balance between persistence and flexibility, which induces intraindividual variability (Akbari Chermahini & Hommel, 2010;Dreisbach & Goschke, 2004;Herd et al, 2014;Müller et al, 2007), and people differ systematically with respect to the efficiency of the degree to which this balance can be achieved (Arbula, Capizzi, Lombardo, & Vallesi, 2016;Babcock & Vallesi, 2017; for a review, see Hommel & Colzato, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…shielding against distraction (cognitive stability), and (b) responding flexibly to failure or to critical changes in the environment (cognitive flexibility; cf., Müller et al, 2007).…”
Section: Affective States and Approach Vs Avoidance Orientations As mentioning
confidence: 99%